2002
DOI: 10.1007/bf02629575
|View full text |Cite
|
Sign up to set email alerts
|

Grooming site preferences determined by lice infection among Japanese macaques in Arashiyama

Abstract: I investigated the effect of the density of louse eggs (Pedicinus obtusus and P. eurygaster) on grooming site preferences in Japanese macaques (Macaca fuscata). Louse eggs were more often found on the outer side of the body (upper back, lower back, outer arms, and outer legs) than on the inner side of the body (chest, belly, inner arms, and inner legs). Japanese macaques were more likely to be groomed on the outer side than the inner side of the body by allogrooming and autogrooming. Such grooming site prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 16 publications
3
91
0
3
Order By: Relevance
“…The reduction in allogrooming following a treatment for ectoparasites confirms the finding of previous correlational studies (e.g. Sanchez-Villagra et al 1998;Perez & Vea 2000;Zamma 2002;Radford & Du Plessis 2006) that allogrooming serves, at least partially, a hygienic role specifically targeted at removing ectoparasites. Surprisingly, individuals experiencing our control treatment, receiving water instead of Advantix, also exhibited decreased parasite loads.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The reduction in allogrooming following a treatment for ectoparasites confirms the finding of previous correlational studies (e.g. Sanchez-Villagra et al 1998;Perez & Vea 2000;Zamma 2002;Radford & Du Plessis 2006) that allogrooming serves, at least partially, a hygienic role specifically targeted at removing ectoparasites. Surprisingly, individuals experiencing our control treatment, receiving water instead of Advantix, also exhibited decreased parasite loads.…”
Section: Discussionsupporting
confidence: 87%
“…Groomers target especially infected or inaccessible regions of their partner's bodies (Perez & Vea 2000;Zamma 2002;Radford & Du Plessis 2006) and, across populations, grooming rate correlated with ectoparasite load, suggesting a hygienic function (SanchezVillagra et al 1998). Reducing ectoparasites' levels reduces the need for hygiene maintenance and could reduce grooming levels.…”
Section: Introductionmentioning
confidence: 99%
“…Others focused on the hygienic function of removal movements. For example, Zamma (2002a) found that in Japanese macaques, the total daily number of removal movements (self-and social grooming) was almost identical to the daily increase in louse eggs. Freeland (1981) compared removal movements between selfand social grooming and found that more particle-removal movements were observed during social grooming than during self-grooming in three species of Cercopithecidae (however, scratching was included in the category of grooming).…”
Section: Introductionmentioning
confidence: 93%
“…Allogrooming is a social behaviour common in primates. It is well known that it has a hygienic function by the removal of ectoparasites (Zamma, 2002) and reduction of social tension by the production of endorphins (Schino et al 1988). It is also linked to group cohesion (Lehmann et al 2007), and the strengthening of links between individuals (Sánchez-Villagra et al 1998).…”
Section: Discussionmentioning
confidence: 99%